PENINGKATAN PRESTASI BELAJAR SISWA DENGAN MENERAPKAN MODEL PEMBELAJARAN DISCOVERY LEARNING PADA PEMBELAJARAN IPS MATERI MASUKNYA HINDU BUDHA DI INDONESIA DI KELAS VII-B SEMESTER 2 SMPN 4 SURABAYA TAHUN PELAJARAN 2023/2024 - Dina Kamilia, Nur; Alfian Rizky, Miftah; Arrahim, Arrahim; Ayu Larasati, Dian; Musrifajaton, Musrifajaton (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The aim of this study is to analyze the use of the Discovery Learning (DL) method. teacher acts as a facilitator who guides students in exploration, discovery, and knowledge construction through direct experience, thus placing students as the main actors in the facilitated learning. Quantitative data collection techniques were conducted through tests. research was conducted in cycles comprising four stages: planning, action implementation, observation, and reflection. Data were obtained through observation of the discussion learning method, observation of student, teacher activities, and formative tests. The subject of improvement was students of class VII-B at SMP 4 Negeri Surabaya, totaling 33 students consisting of 15 males and 18 females. The discovery learning model significantly improves students' learning achievement. In cycle 1, the researcher revised the teaching module and implemented the discovery learning model. In cycle 2, through the improvement and reflection of discovery learning, there was an improvement that reached the established success target. The result is that discovery learning can be an attractive choice of learning method that facilitates subject exploration in students.